The Effects of the Types of Milk (Cow, Goat, Soya) and Enzymes (Rennet, Papain, Bromelain) Toward Cheddar Cheese Production - Arlene, Ariestya; Kristijarti, Anastasia Prima; Ardelia, Ivana (UI Scholars Hub, 2015)
The objectives of this research are to study the effects of different types of milk and enzymes toward the yield and quality (moisture, ash, protein, fat content, and texture) of cheddar cheese and the interaction between those two variables during the process. The types of milk are cow, goat, and soya milk, while the types of enzymes are rennet, papain, and bromelain enzymes. Regarding the procedure, the milk is first pasteurized before CaCl2 and Lactobacillus lactis that acts as the acidifier starter as much as 0.2% (w/v) and 0.5% of the milk volume are added respectively. The amount of enzyme added is appropriate for the determination of enzyme dose. The curd is separated from the whey and then 2.5 grams of salt is added to 100 grams of curd. Afterwards, the curd is pressed until the water content decreases (cheese), then ripened for 1 month. The analyses conducted are moisture, ash, protein, fat content, and texture (hardness). The conclusion is the goat milk and the rennet enzyme are the suitable raw material for cheddar cheese production. Furthermore, different types of milk and enzymes affect the yield. However, there is no interaction between the types of milk and enzymes to the yield.